Effect of natural toxins and adipokinetic hormones on the activity of digestive enzymes in the midgut of the cockroach Periplaneta americana - Karbusová, Nikola; Gautam, Umesh K; Kodrík, Dalibor (Archives of insect biochemistry and physiology, 2019)
This study examined the effect of two natural toxins (a venom from the parasitic wasp Habrobracon hebetor and destruxin A from the entomopathogenic fungus Metarhizium anisopliae), and one pathogen (the entomopathogenic fungus Isaria fumosorosea) on the activity of basic digestive enzymes in the midgut of the cockroach Periplaneta americana. Simultaneously, the role of adipokinetic hormones (AKH) in the digestive processes was evaluated. The results showed that all tested toxins/pathogens elicited stress responses when applied into the cockroach body, as documented by an increase of AKH level in the central nervous system. The venom from H. hebetor showed no effect on digestive enzyme activities in the ceca and midgut in vitro. In addition, infection by I. fumosorosea caused a decrease in activity of all enzymes in the midgut and a variable decrease in activity in the ceca; application of AKHs did not reverse the inhibition. Destruxin A inhibited the activity of all enzymes in the midgut but none in the ceca in vitro; application of AKHs did reverse this inhibition, and no differences between both cockroach AKHs were found. Overall, the results demonstrated the variable effect of the tested toxins/pathogens on the digestive processes of cockroaches as well as the variable ability of AKH to counteract these effects.
Keywords: Insect Hormones; depsipeptidy; Oligopeptides; gastrointestinální trakt; aktivace enzymů; Periplaneta; kyselina pyrrolidonkarboxylová; hmyzí hormony; Pyrrolidonecarboxylic Acid; Gastrointestinal Tract; vosí jedy; Animals; Enzyme Activation; oligopeptidy; Depsipeptides; zvířata; Wasp Venoms